2021
DOI: 10.11152/mu-2542
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic inflammatory pseudotumor mimicking malignancy: the value of differential diagnosis on contrast enhanced ultrasound

Abstract: The aim of this study is to investigate whether the use of contrast enhanced ultrasound (CEUS) can improve the differential diagnostic performance between hepatic inflammatory pseudotumor (HIPT) and other malignant tumors.Material and methods: Forty-four patients with histological proven HIPTs were included in this retrospective study. The features of conventional ultrasound (US) and CEUS were evaluated.Results: Three kinds of enhanced pattern can be seen in the 44 nodules including homogeneous (n=18, 41%), he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Surprisingly, early washout (<60 s) indicated higher probability of IPT. Previous study showed that around 40% of enhanced IPT had quick wash-in and wash-out (6). In our study, 61.9% of IPT patients have early washout, suggesting an even earlier washout in IPT.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Surprisingly, early washout (<60 s) indicated higher probability of IPT. Previous study showed that around 40% of enhanced IPT had quick wash-in and wash-out (6). In our study, 61.9% of IPT patients have early washout, suggesting an even earlier washout in IPT.…”
Section: Discussionsupporting
confidence: 55%
“…Hepatic IPT often presents with atypical symptoms such as abdominal pain, fever, and nonspecific lab results, and therefore diagnosis is challenging and largely relies on the pathologic findings (2,3). Moreover, IPT has a potential for mimicking malignant tumors, such as hepatocellular carcinoma (HCC) (4)(5)(6). Around 60% of IPT patients had to receive surgery because a malignancy was suspected even with the imaging results (3).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations